Komunikasi Dosen Pembimbing Terhadap Kualitas Skripsi Mahasiswa - Metha Lubis; Fika Rahmanita; Marisa Ulfa (Eduka : Jurnal Pendidikan, Hukum, dan Bisnis, 2022)
ABSTRACTThis study aims to determine the effect of supervisor communication on the quality of student thesis. The research method used is a qualitative method using a case study approach. Case studies in qualitative research involve in-depth exploration of the phenomenon being studied through collecting information from various data sources over a certain period (Creswell, 2014; Mertens, 2010). The steps in this research method are: observation, interview, distribution of questionnaires/questionnaires and documentation. Respondents in this study were students of the Economic Education study program at Pamulang University who underwent a thesis trial. The results found from the research are good communication from lecturers and students is able to improve the quality of the thesis. Then the findings in this study there are several barriers in communication.Keywords: supervisor communication; thesis quality; students;